MACULAR PIGMENT OPTICAL DENSITY IS LOWER IN TYPE 2 DIABETES, COMPARED WITH TYPE 1 DIABETES AND NORMAL CONTROLS. Issue 9 (September 2015) - Scanlon, Grainne; Connell, Paul; Ratzlaff, Matthew; Foerg, Brittany; McCartney, Daniel; Murphy, Audrey; O'Connor, Karen; Loughman, James
Abstract : Purpose: This study was designed to investigate the optical density of macular pigment in Type 1 and Type 2 diabetes subjects relative to normal controls. Methods: One hundred and fifty subjects were recruited to the study and divided into one of the three study groups on the basis of their health status, as follows: Group 1: Healthy controls; Group 2: Type 1 diabetes; Group 3: Type 2 diabetes. Macular Pigment Optical Density, at 0.5° of retinal eccentricity, was measured using customized heterochromatic flicker photometry. Dietary intake of macular carotenoids was quantified using a lutein and zeaxanthin food frequency questionnaire. Diabetes type, duration, medication, smoking habits, glycosylated hemoglobin (HbA1C), and serum lipid levels were recorded, whereas visual acuity, body mass index, and diabetic retinopathy grade were measured for each participant. Results: One-way analysis of variance revealed a statistically significant difference in body mass index, age, high-density lipoprotein cholesterol and HbA1C between the three groups ( P < 0.01 for all). Chi-square analysis revealed a statistically significant difference in diabetic retinopathy distribution ( P < 0.01). None of these variables exhibited a statistically significant correlation with macular pigment optical density for any study group ( P > 0.05 for all). There was no difference in dietary carotenoid intake between groups. Macular pigment optical density was lower among Type 2 diabetes subjects (0.33 ± 0.21) compared with Type 1 diabetes (0.49 ± 0.23) and controls (0.48 ± 0.35). General linear model analysis, including age, body mass index, diabetes duration, diabetic retinopathy status, high-density lipoprotein cholesterol, and HbA1C as covariates, revealed a statistically significant effect of diabetes type on macular pigment optical density (F = 2.62; P = 0.04). Conclusion: Macular pigment optical density was statistically significantly lower in Type 2 diabetes compared with Type 1 diabetes and normal controls. Although body mass index was higher in the Type 2 diabetes group, the lower macular pigment optical density levels observed among Type 2 diabetes seem not to be attributable to differences in dietary carotenoid intake or to the specific presence of diabetes, diabetic control, duration, or diabetic retinopathy. Abstract : Lower macular pigment levels observed among the more obese Type 2 diabetes might be explained by competition between adipose and retinal tissue for dietary carotenoids, impaired transport of circulating lutein/zeaxanthin, obesity-induced inflammation, and oxidative stress and/or genetic influence.